Pengaruh ASI Eksklusif, Berat Badan Lahir Rendah, dan Tinggi Badan Ibu terhadap Kejadian Stunting pada Anak di Bawah Usia 2 Tahun di Kabupaten Tapin, Indonesia: Hasil Penelitian - Riza, Ade (Cermin Dunia Kedokteran, 2025)
Background: Stunting affects intergenerational linear growth; short mothers are preceded by stunted childhood and will give birth to babies with low birth weight (LBW). Exclusive breastfeeding is known as one of the factors to prevent stunting. This study was conducted to see the effect of exclusive breastfeeding, history of low birth weight, and mother’s height on the incidence of stunting among below-two-year-old children in Tapin district. Method: Cross-sectional with a bivariate Chi-Square analysis test with odds ratio to assess the risk. Result: The results showed that the incidence of stunting was associated with the mother’s height (p=0.002, OR 8.325, 95% CI 2.117–32.741). Exclusive breastfeeding and low birth weight were not associated with the incidence of stunting (p=0.751, OR 1.303, 95%CI 0.454-3.738 for exclusive breastfeeding and p=0.201, OR 2.222, 95%CI 0.849–5.818 for LBW). Conclusion: Mother’s height affects the incidence of stunting in below-two-year-old children in Tapin district.